PEMAHAMAN UMAT PAROKI TRINITAS MAHAKUDUS PASLATEN TENTANG TINDAKAN LITURGIS DALAM EKARISTI - Lontoh, Raymond; Mayokan, Eduard; Raga, Vinsensius (Pineleng Theological Review, 2024)
This study aims to know and understand the liturgical actions that occur in the parish of the Holy Trinity Paslaten. Then the researcher proceeds to the search for the level of liturgical understanding, especially the liturgical action of the people. In the end, we will know how liturgical teaching compares with the liturgical understanding and liturgical action of the people. The methods used are observation, interviews, and literature studies. Observation is made to observe liturgical actions that are carried out by people in liturgical celebrations. Interviews were conducted to determine the level of understanding and meaning of the people regarding the liturgical actions they carried out. A literature study was conducted to find out about the official teaching of the Church regarding liturgical action. Important results found are: the practice of liturgical action is often incompatible with teaching. The practice of the sign of the cross, standing, kneeling, and sitting is often not done properly and correctly. Such liturgical practices often also lose meaning and significance. However, there are still people who faithfully and passionately carry out these liturgical acts. From these results, it can be concluded that liturgical actions have not been fully carried out properly and correctly, nor have they often lost their meaning. The pastoral recommendations offered are good liturgical teaching and complete facilities to support liturgical action.